(untitled) (Bangladesh Agronomy Journal, 2015)
An experiment was conducted at the net house of Department of Agronomy, Bangladesh Agricultural University, Mymensingh from July to December 2012to investigate the ameliorative effect of green manure and gypsum application on the yield of transplant Aman rice variety BRRI dhan40 under various levels salinity stress. Sodium chloride induced salinity was imposed at tillering stage of plant development. The levels of salinity were 0, 25 and 50 mM NaCl. Green manure @ 0, 5 and 10 t ha gypsum @ 0 and 1 g kg-1 and 1 soil were applied to ameliorate the salinity stress effect. 1 g kg-1 soil were applied to ameliorate the salinity stress effect. Results revealed that the different levels of salinity had significant adverse effect on plant height, number of tillers hill-1, number of effective tillers hill-1, number of ineffective tillers hill-1, 1000-grain weight, grain yield, biological yield and harvest index (HI). All the plants were affected badly when they were exposed to salinity level of 50 mM NaCl. Application of green manure and gypsum helped them ameiorate salinity either individually or in combination at all salinity levels. Grain yield reduction at 50 mM salinity level was 38.64% compared to control which was minimized to 19.04% by the application of green manure @ 10 t ha-1. Grain yield reduction was also minimized from 37.08% to 27% at the same level of salinity by the application of gypsum@ 1 g kg-1soil. Similar amelioration effect was also observed in case of straw yield. The amelioration was improved further when both green manure and gypsum were applied. Without any salinity stress grain yield was 4.49 t ha-1, which was reduced to 2.61 t ha-1 (41.87% reduction) when the crop was stressed with 50 mM salinity. Application of green manure @ 10 t ha-1 and gypsum @ 1 g kg-1 soil improved grain yield to 4.00 t ha-1, where yield reduction was just 10.91%. Similar improvement was also found in straw yield. The results of the study conclude that salinity stress in transplant Aman rice var. BRRI dhan40 could successfully be ameliorated through application of green manure@ 10 t ha-1 and gypsum@ 1 g kg-1 soil. Bangladesh Agron. J. 2014, 17(1): 1-10